(untitled) (Journal of Rashid Latif Medical College, 2023)
Microbes and viruses shape civilizations. Every hour our immune systems fend off microbialattacks both from within and without. Immune system and its programmability are nature’s marvelous giftpackage that has helped us survive and thrive in spectacular way. Performing silently and constantly, thesebiological defenses are remarkably adaptable in both recognizing and understanding the invader foreverbesides conferring lifelong immunity against them.